The acute symptoms of sport-related concussion: diagnosis and on-field management - Putukian, M. (Clinics in Sports Medicine, 2011)
Sport-related concussion is a common injury that occurs in a variety of sports. In recent years, more attention has been focused on the importance of this injury as well as the long-term complications of unrecognized, repetitive, and/or severe injury. The acute presentation of concussion as well as the diagnosis of concussion is often straightforward and obvious, but it can also be subtle and difficult to discern. Most injuries are short lived with complete recovery within a couple of weeks, with a small minority taking several months to resolve. Unfortunately, it is difficult to predict which injuries will linger. This article discusses the on-field presentation, diagnosis, and management of sport-related concussion. It is important to have a concussion protocol for high-risk sports, including a preseason and postinjury assessment, and an individualized yet comprehensive approach that includes evaluating symptoms, and a neurologic examination that includes cognitive function and balance testing. A multifaceted approach to the evaluation and diagnosis of concussion is endorsed for the optimal management of this injury.